No Resistance and Improved Renal and Bone Profiles with a Single-Table Regimen of D/C/F/TAF - Rizzo, Toni (MD Conference Express, 2014)
Darunavir is a protease inhibitor (PI) dosed as a single daily tablet. PIs have a high genetic barrier to resistance, but a PI-based single-tablet regimen has not been available. This article presents the results of the week 48 analysis of the Safety and Efficacy of Darunavir/Cobicistat/Emtricitabine/GS-7340 Single Tablet Regimen Versus Cobicistat-Boosted Darunavir Plus Emtricitabine/Tenofovir Disoproxil Fumarate Fixed Dose Combination in HIV-1 Infected, Antiretroviral Treatment Naïve Adults [GS-US-299-0102; NCT01565850].